Risk Factors, Patterns, and Outcomes of Late Recurrence After Liver Resection for Hepatocellular Carcinoma: A Multicenter Study From China - Xu, Xin-Fei; Xing, Hao; Han, Jun; Li, Zhen-Li; Lau, Wan-Yee; Zhou, Ya-Hao; Gu, Wei-Min; Wang, Hong; Chen, Ting-Hao; Zeng, Yong-Yi; Li, Chao; Wu, Meng-Chao; et al. (JAMA surgery, 2019)
IMPORTANCE: Late recurrence (more than 2 years) after liver resection for hepatocellular carcinoma (HCC) is generally considered as a multicentric tumor or a de novo cancer. OBJECTIVE: To investigate the risk factors, patterns, and outcomes of late recurrence after curative liver resection for HCC. DESIGN, SETTING, AND PARTICIPANTS: This study was a multicenter retrospective analysis of patients who underwent curative liver resection for HCC at 6 hospitals in China from January 2001 to December 2015. Among 734 patients who were alive and free of recurrence at 2 years after resection, 303 patients developed late recurrence. Data were analyzed from June 2017 to February 2018. INTERVENTIONS: Liver resection for HCC. MAIN OUTCOMES AND MEASURES: Risk factors of late recurrence as well as patterns, treatments, and long-term outcomes of patients with late recurrence. Univariate and multivariate Cox regression analyses were performed to identify independent risk factors of late recurrence. RESULTS: Of the included 734 patients, 652 (88.8%) were male, and the mean (SD) age was 51.0 (10.3) years. At a median (interquartile range) follow-up of 78.0 (52.8-112.5) months, 303 patients (41.3%) developed late recurrence. Multivariate analysis revealed that male sex, cirrhosis, multiple tumors, satellite nodules, tumor size greater than 5 cm, and macroscopic and microscopic vascular invasion were independent risk factors of late recurrence. Of the 303 patients with late recurrence, 273 (90.1%) had only intrahepatic recurrence, 30 (9.9%) had both intrahepatic and extrahepatic recurrence, and none had only extrahepatic recurrence. Potentially curative treatments were given to 165 of 303 patients (54.5%) with late recurrence, which included reresection, transplant, and local ablation. Multivariate Cox regression analysis showed that regular surveillance for postoperative recurrence (hazard ratio [HR], 0.470; 95% CI, 0.310-0.713; P = .001), cirrhosis (HR, 1.381; 95% CI, 1.049-1.854; P = .02), portal hypertension (HR, 2.424; 95% CI, 1.644-3.574; P < .001), Child-Pugh grade of B or C (HR, 1.376; 95% CI, 1.153-1.674; P < .001), Barcelona Clinic Liver Cancer stage B (HR, 1.304; 95% CI, 1.007-1.708; P = .04) and stage C (HR, 2.037; 95% CI, 1.583-2.842; P < .001), and potentially curative treatment (HR, 0.443; 95% CI, 0.297-0.661; P < .001) were independent predictors of overall survival for patients with late recurrence. CONCLUSIONS AND RELEVANCE: Late recurrence after HCC resection was associated with sex, cirrhosis, and several aggressive tumor characteristics of the initial HCC. The patterns of late recurrence suggested surveillance for recurrence after 2 years of surgery should be targeted to the liver. Postoperative surveillance improved the chance of potentially curative treatments, with improved survival outcomes in patients with late recurrence.